Design and simulation of grating coupler for silicon photonics - Ni, Jiayi (Nanyang Technological University, 2022)
Over the last few decades, silicon photonics have transformed the field of optics with its ability to mass produce extremely small components with low-cost manufacturing. An important issue regarding this technology is the difficulty in coupling light from the optical fiber to the silicon waveguide devices. In this report, we will discuss the methods of coupling and narrow it down to grating couplers. We will also discuss various optimization methods and simulations done by previous studies. Finally, we will discuss on the results from Finite Difference Time Domain (FDTD) simulations and conclude on the methods used. In this report, a grating coupling efficiency of 80% for 15500nm was achieved with a grating coupler with an aluminium backreflector.